Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3390/plants9070837
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Carbon Compounds Modulate Tomato Root Development

Abstract: NO3− is not only a nutrient, but also a signaling compound that plays an important role in several plant processes, like root development. The present study aimed to investigate the effect of three different exogenous C compounds (sucrose, glucose, 2-oxoglutarate) added to NO3− nutrition on C/N, auxin and antioxidant metabolisms in 10-day-old tomato seedlings. Sucrose and glucose supplementation enhanced primary root (PR) length, lateral root number and root density, while 2-oxoglutarate negatively aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 74 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…It has been shown that N addition promotes N nutrition in plants under salt stress 47 . It was also found that the addition of 2-oxoglutarate to NO 3 containing nutrients enhanced the expression of NiR, GDH and antioxidant gene SOD in potato roots 58 . Here, foliar N and 2-oxoglutarate significantly increased GS and GOGAT activities in both soybean cultivars under drought stress.…”
Section: Impacts Of Foliar N Plus 2-oxoglutarate On N Metabolism Duri...mentioning
confidence: 91%
“…It has been shown that N addition promotes N nutrition in plants under salt stress 47 . It was also found that the addition of 2-oxoglutarate to NO 3 containing nutrients enhanced the expression of NiR, GDH and antioxidant gene SOD in potato roots 58 . Here, foliar N and 2-oxoglutarate significantly increased GS and GOGAT activities in both soybean cultivars under drought stress.…”
Section: Impacts Of Foliar N Plus 2-oxoglutarate On N Metabolism Duri...mentioning
confidence: 91%
“…To this end, tomato cv. Marglobe seeds were sterilized following the protocol described by González-Hernández [24]. Briefly, the seeds were cleaned with sodium hypochlorite (75% v/v) containing 0.1% of Tween 20 (Sigma-Aldrich, San Luis, MO, USA) for 8 min and then washed with sterilized distilled water for 5 min four times.…”
Section: Determination Of Root Developmentmentioning
confidence: 99%
“…González-Hernández et al (2020) [ 12 ] have studied the effect of sucrose, glucose and 2-oxoglutarate on nitrate nutrition. Their results contribute to a better understanding of how these C sources can modulate N uptake and the expression of C/N genes, auxins, and antioxidants.…”
Section: Carbon Supply and Its Implication In N Assimilationmentioning
confidence: 99%